Dissemination of child abuse clinical decision support: Moving beyond a single electronic health record. (March 2021) - McGinn, Thomas; Feldstein, David A.; Barata, Isabel; Heineman, Emily; Ross, Joshua; Kaplan, Dana; Richardson, Safiya; Knox, Barbara; Palm, Amanda; Bullaro, Francesca; Kuehnel, Nicholas; Park, Linda; et al.
Highlights: EHR-embedded CA-CDS can improve child abuse recognition, evaluation and reporting. Dissemination of CA-CDS into different EHRs and hospital systems can be done. Dissemination is cumbersome and time-consuming. Alternative approaches to dissemination should be evaluated. Abstract: Background: Child maltreatment is a leading cause of pediatric morbidity and mortality. We previously reported on development and implementation of a child abuse clinical decision support system (CA-CDSS) in the Cerner electronic health record (EHR). Our objective was to develop a CA-CDSS in two different EHRs. Methods: Using the CA-CDSS in Cerner as a template, CA-CDSSs were developed for use in four hospitals in the Northwell Health system who use Allscripts and two hospitals in the University of Wisconsin health system who use Epic. Each system had a combination of triggers, alerts and child abuse-specific order sets. Usability evaluation was done prior to launch of the CA-CDSS. Results: Over an 18-month period, a CA-CDSS was embedded into Epic and Allscripts at two hospital systems. The CA-CDSSs vary significantly from each other in terms of the type of triggers which were able to be used, the type of alert, the ability of the alert to link directly to child abuse-specific order sets and the order sets themselves. Conclusions: Dissemination of CA-CDSS from one EHR into the EHR in other health care systems is possible but time-consuming and needs to be adapted to the strengths and limitations of the specific EHR. Site-specific usability evaluation, buy-in of multiple stakeholder groups and significant information technology support are needed. These barriers limit scalability and widespread dissemination of CA-CDSS.